Re-Thinking Malaria and Other Infectious Diseases in the Borneo Malay World: Texts and Contexts (Malay Literature, 2022)
The COVID-19 pandemic has made people aware of the importance of attention to infectious diseases. Malaria is one of the infectious diseases in the tropics and is a disease that many literary writers have depicted in their works. Malaria and other infectious diseases emerged and spread very quickly among workers since the colonial period, when large-scale plantations and mining in the Malay World was carried out, primarily supported by the construction of roads connecting the plantation and mining areas. This article will analyse the emergence of discourse about the spread of malaria and other infectious diseases in literary works, especially in short stories about the Malay World of Borneo. This study will also analyse two works by two authors, namely “Penari Dari Kutai” in Dunia Sukab, a short stories collection by Seno Gumira Adjidharma (2015), and “Kampung Beremai” in Kayu Naga short stories collection by Korrie Layun Rampan (2007). The two works tell the story of the spread of malaria and other infectious diseases in the Borneo Malay World, especially in the East Kalimantan region of Indonesia. The method used in this study is based on close reading method with data collection and data analysis through textual analysis or document analysis. The results of this study demonstrate that literary works about the of Borneo Malay World also record the presence of infectious diseases, such as malaria, syphilis, and the plague, which coincide with forest clearing for plantation and mining activities.Full text: PDF